Understanding Society at 10 Years. (20th September 2020) - Platt, Lucinda; Knies, Gundi; Luthra, Renee; Nandi, Alita; Benzeval, Michaela
Abstract: Understanding Society : The UK Household Longitudinal Study (UKHLS) has now been collecting a range of data from its nationally representative sample of participants for 10 years. This significant 'birthday' offers a moment to reflect on its contribution to sociological research, and on its current and future potential for fundamental and cutting-edge sociological analysis. While the study shares many features with other longer-standing household panel studies, including its direct predecessor the British Household Panel Survey (BHPS), it incorporated from the outset distinctive features that make it particularly valuable for analysis in specific fields, including biosocial research, ethnicity and migration studies, and analyses of the interplay between environmental, social and institutional contexts and individual characteristics. Understanding Society has incorporated methodological development and innovation since its inception, which has facilitated more extensive forms of data collection.